2010
DOI: 10.1016/j.micres.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Lactobacillus acidophilus and Lactobacillus casei against methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a multidrug-resistant microorganism and the principal nosocomial pathogen worldwide. The antibacterial activity of lactic acid bacteria against MRSA from ten human clinical isolates as well as MRSA standard strain ATCC 43300 was tested in vitro. The Lactobacillus (Lb.) strains (Lb. acidophilus CL1285(®) and Lb. casei LBC80R) as pure cultures, which came from commercial food products were employed. The growth inhibitory effect produced by the antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…They showed that Lactobacillus acidophilus produces antimicrobial compounds that inhibit MRSA growth to the extent that after 24 hours incubation of probiotic bacteria and pathogens at 37°C, there was 99% decrease in pathogens population. Also, Lactobacillus casei by producing different compounds such as lactic acid has bactericidal effect on MRSA pathogens (25). In 2012, Guo et al studied the anti-fungal effect of 4 Lactobacillus types against Microsporum canis, Microsporum gypseum and Epidermophyton flocossum by the agar diffusion method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that Lactobacillus acidophilus produces antimicrobial compounds that inhibit MRSA growth to the extent that after 24 hours incubation of probiotic bacteria and pathogens at 37°C, there was 99% decrease in pathogens population. Also, Lactobacillus casei by producing different compounds such as lactic acid has bactericidal effect on MRSA pathogens (25). In 2012, Guo et al studied the anti-fungal effect of 4 Lactobacillus types against Microsporum canis, Microsporum gypseum and Epidermophyton flocossum by the agar diffusion method.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was repeated six times and then the samples were checked regarding their appearance and stability (25).…”
Section: Freezing and Thawingmentioning
confidence: 99%
“…The portion were stored at 5°C for 48 h and then at 25°C for 48 h. The procedure was repeated 6 times and their stability and appearance were evaluated [22].…”
Section: Thermal Cycle Testmentioning
confidence: 99%
“…Accordingly, they are commonly associated with nutritious environments like foods, decaying material and the mucosal surfaces of the gastrointestinal and urogenital tract [12][13][14], where they enhance the host protection against pathogens [13]. Their antagonistic and inhibitory properties are due to the competition for nutrients and the production of one or more antimicrobially active metabolites such as organic acids (lactic and acetic acid), hydrogen peroxide, and antimicrobial peptides like bacteriocins [8][9][10][11][15][16][17]. Bacteriocins are ribosomally synthesized peptides that exert their antimicrobial activity against either strains of the same species as the bacteriocin producer (narrow range), or to more distantly related species (broad range) [7,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…An important reason for research on LAB based bacteriocins is due to their activity at nanomolar concentrations against number of bacterial pathogens [1,3,5,6,19,20]. Some bacteriocins even exhibit their activities against multidrug-resistant nosocomial pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci [VRE,17,21]. Thus they also may have some big potential in medical and veterinary applications.…”
Section: Introductionmentioning
confidence: 99%